Taxonomic and nomenclatural changes in three species of Pterostichus Bonelli (Coleoptera: Carabidae) from the Far East - Sasakawa, Kôji; Berlov, Oleg; Okuzaki, Yutaka (Zootaxa, 2020)
The ground beetle genus Pterostichus Bonelli has diversified in regions including the Far East, but taxonomic issues remain even at the species level. This study presents taxonomic and nomenclatural changes in three species of Pterostichus from the Far East: P. (Petrophilus) eximius Morawitz, P. (Lenapterus) wellschmiedi Kirschenhofer, and P. (L.) subrugosus Straneo. The analyses are based on comparative studies of the endophallus of male genitalia, which is taxonomically useful in Carabidae but has not been examined in these species. The first species, P. eximius, has been treated as a monotypic species that is widely distributed in Eastern Siberia, the Russian Far East, and adjacent regions, but our results revealed that populations from Rishiri-tô and the Sakhalin islands are distinct from the nominotypical population from Transbaikalia. The name for the Sakhalin population, which was synonymized with P. eximius, is reinstated as subspecies P. eximius sachalinensis stat. nov., and the Rishiri-tô population is described as Pterostichus eximius rishiridakensis ssp. nov. Conspecificity (syn. nov.) was confirmed for P. wellschmiedi, which was described from southern Sakhalin, and P. marginatus Matsumura, which was described earlier from southern Sakhalin. No conspicuous differences in the endophallus structure were found between P. subrugosus, which was described from Hokkaidô, and P. marginatus, although differences are recognized in the elytral sculptures and in the metallic luster of the dorsal surface. The taxon was thus downgraded to subspecies P. marginatus subrugosus stat. nov.